RECONCILIATION OF PROFESSIONAL, PRIVATE AND FAMILY LIFE UNDER THE EUROPEAN UNION LAW - Klimašauskienė, Inga (Teisė, 2015)
European Union (EU) primary and secondary law does not provide an explicit definition of the reconciliation of professional, private and family life. The ambiguity of this definition can be seen both in the terminology and in the content of it.EU legislators and policy-makers often use the term “work-life balance” instead of reconciliation. Nevertheless, the fundamental legislation, i.e. the Charter of Fundamental Rights of the EU, which forms a part of EU primary law (since 1 December 2009), in using the terminology “reconciliation”, considers it reasonable to use the latter terminology rather than “work-life balance”. In addition, in EU legislation and policy a narrow expression can be found – reconciliation of work and family life, and a broader expression – reconciliation of professional, private and family life. The research illustrates, however, that it is not clear as to what exactly is being attempted to reconcile – work with family or (and) with private obligations? Furthermore, the wording used in the discussed definition creates ambiguity as to what structure of “family” and “private” life the provision is addressed.An examination of the Court of Justice of the European Union, as well as the European Court of Human Rights case law shows that reconciliation is an attempt to broaden the scope. The “family” in terms of the reconciliation right is to be interpreted as encompassing all significant relatives in a person’s personal life, irrespective of formal relationships. Reconciliation is a multi-edged concept and involves a sophisticated framework: 1) pregnancy, birth, maternity and paternity, 2) flexible working arrangements, 3) care of adults, the elderly and other dependents. Regrettably, however, the legal measures are still very limited and are mostly focused on family needs, and therefore do not wholly justify the extended notion of reconciliation.